Scalable Liquid Shear‐Driven Fabrication of Polymer Nanofibers. (18th March 2015) - Smoukov, Stoyan K.; Tian, Tian; Vitchuli, Narendiran; Gangwal, Sumit; Geisen, Pete; Wright, Miles; Shim, Eunkyoung; Marquez, Manuel; Fowler, Jeffrey; Velev, Orlin D.
<x xml:space="preserve">Abstract</x> A simple process for batch or continuous formation of polymer nanofibers and other nanomaterials in the bulk of a sheared fluid medium is introduced. The process may be of high value to commercial nanotechnology, as it can be easily scaled up to the fabrication of staple nanofibers at rates that may exceed tens of kilograms per hour. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>